2009
DOI: 10.1007/s12010-009-8526-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Bacterial-Derived Toxins to Immortal Lung Epithelial and Macrophage Cells

Abstract: Health risks associated with inhalation and deposition of biological materials have been a topic of great concern due to highly publicized cases of inhalation anthrax, of new regulations on the release of particulate matter, and to increased concerns on the hazards of indoor air pollution. Here, we present an evaluation of the sensitivity of two immortal cell lines (A549, human lung carcinoma epithelia) and NR8383 (rat alveolar macrophages) to a variety of bacterial-derived inhalation hazards and simulants inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…The results of Annexin V/PI flow cytometry confirmed that both GT and FUM alone as well as in combination induced apoptosis rather than necrosis in both A549 and L132 epithelial cells. Our results are consistent with previous reports in respect of GT and FUM 23,24,40 . Apoptosis can be initiated by one of two pathways, caspase-8-associated death receptor pathway, i.e.…”
Section: Discussionsupporting
confidence: 94%
“…The results of Annexin V/PI flow cytometry confirmed that both GT and FUM alone as well as in combination induced apoptosis rather than necrosis in both A549 and L132 epithelial cells. Our results are consistent with previous reports in respect of GT and FUM 23,24,40 . Apoptosis can be initiated by one of two pathways, caspase-8-associated death receptor pathway, i.e.…”
Section: Discussionsupporting
confidence: 94%
“…Next, a dose-response and time-course analysis of SLO cytotoxicity in HEp-2 and A549 cells grown in the FBS-deprived medium was performed. According to literature ( 38 ), cells treatment with SLO caused a dose- and time-dependent decrease in cell survival ( Figure 2A ). On the basis of the IC50 values calculated ( Figure 2B ), we treated HEp-2 and A549 cells with 600 U/mL SLO for 0.5, 6, and 24 h. HEp-2 cells pre-incubated with tolerated doses of HSA ( Figure S6 ) before exposure to 600 U/mL SLO for 0.5 h showed a cell viability increase of ~15% at 1.0×10 −5 M and 1.0×10 −4 M HSA ( P <0.0001; IC50 >5000 U/mL), compared to HSA-untreated cells (IC50 = 582 U/mL) ( Figures 2C, D ).…”
Section: Resultssupporting
confidence: 70%
“…It is a member of the epipolythiodioxopiperazine family of fungal toxins, which carries an internal disulfide bridge that is essential for its function (Scharf et al, 2012; Schlam et al, 2016). Gliotoxin has a wide range of immunomodulatory capabilities, inhibiting the phagocytosis of macrophages and the immune functions of other immune cells (Nishida et al, 2005; Peterson et al, 2010; Schlam et al, 2016). Gliotoxin is thought to indirectly inhibit inducible NF-κB activity by preventing the proteosomal degradation of its inhibitor, IκB, which consequently induces host-cell apoptosis (Kroll et al, 1999; Stanzani et al, 2005; Geissler et al, 2013; Scharf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, gliotoxin has been detected not only in the blood and alveolar lavage fluid of patients with IA, but also in the moist environments, including surfaces of objects contaminated with the fungus and even in the air or ventilation system (Peterson et al, 2010; Geissler et al, 2013). In one study, around 0.43–1.12 pg/mg gliotoxin in building material and 400 pg/cm 2 in the dust have been detected (Thrasher and Crawley, 2009).…”
Section: Introductionmentioning
confidence: 99%